Fifty Shades of Scandium: Comparative Study of PET Capabilities Using Sc-43 and Sc-44 with Respect to Conventional Clinical Radionuclides - Thiago V. M. Lima; Silvano Gnesin; Klaus Strobel; Maria del Sol Pérez; Justus E. Roos; Cristina Müller; Nicholas P. van der Meulen (Diagnostics, 2021)
Scandium-44 has been proposed as a valuable radionuclide for Positron Emission Tomography (PET). Recently, scandium-43 was introduced as a more favorable option, as it does not emit high-energy γ-radiation; however, its currently employed production method results in a mixture of scandium-43 and scandium-44. The interest in new radionuclides for diagnostic nuclear medicine critically depends on the option for image-based quantification. We aimed to evaluate and compare the quantitative capabilities of scandium-43/scandium-44 in a commercial PET/CT device with respect to more conventional clinical radionuclides (fluorine-18 and gallium-68). With this purpose, we characterized and compared quantitative PET data from a mixture of scandium-43/scandium-44 (~68% scandium-43), scandium-44, fluorine-18 and gallium-68, respectively. A NEMA image-quality phantom was filled with the different radionuclides using clinical-relevant lesion-to-background activity concentration ratios; images were acquired in a Siemens Biograph Vision PET/CT. Quantitative accuracy with scandium-43/scandium-44 in the phantom’s background was within 9%, which is in agreement with fluorine-18-based PET standards. Coefficient of variance (COV) was 6.32% and signal recovery in the lesions provided RCmax (recovery coefficient) values of 0.66, 0.90, 1.03, 1.04, 1.12 and 1.11 for lesions of 10-, 13-, 17-, 22-, 28- and 37-mm diameter, respectively. These results are in agreement with EARL reference values for fluorine-18 PET. The results in this work showed that accurate quantitative scandium-43/44 PET/CT is achievable in commercial devices. This may promote the future introduction of scandium-43/44-labelled radiopharmaceuticals into clinical use.